Mite species (Acari: Mesostigmata) new and rare to Polish fauna, inhabiting the soil of broadleaved forests dominated by small-leaved lime (Tilia cordata Mill.) in Kwidzyn Forest District (N Poland) - FALEŃCZYK-KOZIRÓG, KATARZYNA; MARQUARDT, TOMASZ; KACZMAREK, SŁAWOMIR (Biological Letters, 2015)
During a two-year study on mites of the order Mesostigmata in broadleaved forest stands dominated by small-leaved lime (Tilia cordata Mill.), 117 mite species were identified. Among them, 3 had been so far rarely recorded in Poland (Haemogamasus nidi, Stylochirus rovenensis and Eugamasus crassitarsis) and 2 were classified as new to the Polish fauna (Veigaia sibirica and Digamasellus perpusillus).